ประสิทธิผลของโปรแกรมการฝึกสติบำบัดต่อการกลับมาเสพซ้ำในกลุ่มผู้เข้ารับการบำบัดการติดสารเมทแอมเฟตามีน - วรรณจรี มณีแสง (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study was a non-concurrent controlled intervention study. The objective of this study was to study the effectiveness of Mindfulness – Based Therapy and Counseling program (MBTC) in conjunction with the rehabilitation process using the FAST model program, and compared to using the FAST model program alone. Existing programs were used to determine methamphetamine relapse among 70 patients with methamphetamine use disorder who attended rehabilitation therapy. In the process, the samples were entered and rejected and divided into two groups: the control group (group treated with FAST model program), and the experimental group (group treated with MBTC program in conjunction with FAST Model program). Both groups consisted of 35 people each. The experimental group was to practice mindfulness for 8 weeks, approximately 1 hour per week. The results of both groups were then followed up for 6 months after discharge. The results of data analysis using generalized mixed model statistics showed that, after the 6-month follow-up period after discharge, the experimental group had a statistically significantly lower mean score of craving than the control group (7.89 points, 95%CI = -15.47, -0.32). It was found that the experimental group had a statistically significant proportion of those who was detected urine positive for methamphetamine  (5/35 people) less than the control group (16/35 people) (chi-square test; p-value = 0.004). It was also found that the experimental group had less stress (7.44 score, 95%CI = -12.21, -2.67) and depression (2.96 score, 95%CI = -5.31, -0.6) than the control group. At the same time, the experimental group was statistically significantly more mindful than the control group (12.86 points, 95%CI = 9.37, 16.35).It could be concluded that the use of MBTC in combination with FAST model during a 6-month follow-up of treatment reduced relapse among methamphetamine addicts better than FAST model alone.